WOMEN SPEECH BY NICHOLAS SPARKS Ã¢â‚¬Å“THE LONGEST RIDEÃ¢â‚¬Â - IKA TRISNANTASARI; WAHYU PRASBUDIANTO MURSADI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
This study investigates the meaning of women speech. The researcher interested to analyze women speech by the main character in the novel The Longest Ride literary works of Nicholas Sparks because the main character in the novel The Longest Ride interpreted of women in real life. The researcher purposed to find out the meaning of women speech that always became a mystery to all of the men when they communicated in love relationship. This analyzed, the researcher used to intrinsic approach to analyzing women speech by the main character in the novel The Longest Ride. The researcher used to extrinsic with a qualitative approach to analyze one by one the meaning of women speech by the main character in the novel The Longest Ride. The researcher used a descriptive qualitative method to explain the meaning of women speech by the main character in the novel The Longest Ride with took citation proof in the novel The Longest Ride. The researcher analyzed types of women speech was like less direct or assertive direct, trouble talk, emotional expressivity, and intimacy that found by citation in the novel The Longest Ride. After this research, the researcher got the point if the women speech had more types of women speech and had a more different meaning that interpreted by the main character in the novel The Longest Ride.